Intention to purchase products under volume discount scheme: a conceptual model and research propositions - Iranmanesh, Mohammad; Jayaraman, Krishnaswamy; Ismail, Ishak (Business: Theory and Practice, 2014)
Many standard brands sell products under the volume discount scheme (VDS) as more and more consumers are fond of purchasing products under this scheme. Despite volume discount being commonly practiced, there is a dearth of research, both conceptual and empirical, focusing on purchase characteristics factors and consumer internal evaluation concerning the purchase of products under VDS. To attempt to fill this void, this article develops a conceptual model on VDS with the intention of delineating the influence of the purchase characteristics factors on the consumer intention to purchase products under VDS and provides an explanation of their effects through consumer internal evaluation. Finally, the authors discuss the managerial implications of their research and offer guidelines for future empirical research.